2015
DOI: 10.1159/000381808
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Markers AFP, AFP-L3, and DCP in Hepatocellular Carcinoma Refractory to Transcatheter Arterial Chemoembolization

Abstract: Background/Aim: We examined tumor marker levels to assess in more detail transcatheter arterial chemoembolization (TACE)-refractory hepatocellular carcinoma (HCC). Materials and Methods: We enrolled patients treated from 2000 to 2011 for HCC beyond the Milan criteria who had good hepatic reserve function (Child-Pugh A) and no portal vein thrombosis or metastases (n = 154). The modified criteria for being TACE-refractory according to the Liver Cancer Study Group of Japan (m-LCSGJ), from which the tumor marker i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 20 publications
3
25
0
Order By: Relevance
“…Second, we also validated the widely reported fact that initial response is critical for patients who undergo TACE . In the present study, patients without recurrence within 1 year after the initial TACE showed the longest survival.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Second, we also validated the widely reported fact that initial response is critical for patients who undergo TACE . In the present study, patients without recurrence within 1 year after the initial TACE showed the longest survival.…”
Section: Discussionsupporting
confidence: 84%
“…Second, we also validated the widely reported fact that initial response is critical for patients who undergo TACE. [18][19][20][21][22] In the present study, patients without recurrence within 1 year after the initial TACE showed the longest survival. Although tumor response to TACE is one of the most important factors that guides the next treatment decision, the rate of liver function deterioration is also important because some treatment options, such as resection and chemotherapy, are safe only when liver function is preserved.…”
Section: Ntermediate-stage or Bclc Stage B Hcc Consistssupporting
confidence: 52%
“…If ALBI-grade is 2 at diagnosis of BCLC-B and unresectable HCC, then TACErefractory status should be assessed more strictly for avoiding a worsening hepatic function more with continuing TACE, so as to not lose the chance of switching to a molecular target drug. High levels of tumor markers [35] (positive for 2 of the following factors: alphafetoprotein >100 ng/mL, fucosylated alpha-fetoprotein >10%, des-gamma carboxyprothrombin >100 mAU/ mL) after 2 TACE procedures was reported to be poor as a prognostic marker in HCC patients with BCLC-B [36] , thus it is important to focus on malignant potential and maintain hepatic function other than response in such patients.…”
Section: Discussionmentioning
confidence: 99%
“…Among intermediate-stage HCC patients treated with TACE, Takayasu et al [12] noted that the overall median period of survival was 3.3 years and that the 5-year survival rate was 34%. However, few systems for predicting the prognosis of patients with intermediate-stage HCC treated with TACE have been proposed [36,37,38]. In addition to the good capability for predicting prognosis and subsequent subdivision of all patients with intermediate-stage HCC, the present MICAN criteria might be also simple and useful for prediction of prognosis, specifically in those treated with TACE, and future additional studies for confirmation will be needed.…”
Section: Discussionmentioning
confidence: 99%